Dynamic linkages of Asian stock markets - Baharumshah, Ahmad Zubaidi; Sarmidi, Tamat; Tan, Hui Boon (Taylor and Francis Group, 2003)
This study examines the dynamic interrelationship among the major stock markets and in the four Asian markets (Malaysia, Thailand, Taiwan and South Korea), both in the short run and in the long run. To investigate the impact of financial reforms and the Asian financial crisis on these markets, we split the sample into three sub-periods: pre-liberalization (1988-91), post-liberalization (1992-96) and post-crisis (1997-99) periods. The empirical results suggest that all the Asian markets are closely linked with each other and with the world capital markets, namely those of the US and Japan, over the post-liberalization era. Overall, the evidence shows that the degree of integration between the Asian emerging markets and the US increased following the deregulation period, and that the relationship has intensified since the onset of the Asian crisis. There is no evidence to show that Japan has overtaken the US in dominating the Asian equity markets. In addition, our results show that the interrelationship among the Asian national markets has been affected by the crisis. Specifically, the crisis-affected countries of Malaysia and Thailand are increasingly interrelated with South Korea and Taiwan in the post-crash period.